2011
DOI: 10.1002/ajh.22183
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function testing prior to reduced intensity conditioning allogeneic stem cell transplantation in an unselected patient cohort predicts posttransplantation pulmonary complications and outcome

Abstract: Pretransplant pulmonary function tests (PFTs) have been checked mostly in myeloablative allogeneic stem cell transplantation (Allo-SCT). Their value in the setting of reduced intensity conditioning Allo-SCT (Allo-RIC) has been less explored. We retrospectively evaluated the predictive value of PFTs on posttransplant pulmonary complications (PPC) and outcomes in 195 consecutive Allo-RIC patients, based on fludarabine plus busulphan or melphalan. PFT parameters included forced vital capacity (FVC), forced expira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
5
24
0
Order By: Relevance
“…The present study confirmed that pulmonary function prior to allo‐HCT is a valuable predictor of patient mortality following allo‐HCT, which is consistent with previous reports . Notably, the small airway disease parameter trueV˙50/trueV˙25 is the strongest predictor of survival; it has a much higher predictive value than %FEV1.0 and FEV 1.0/FVC, which mainly reflect central airway obstruction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study confirmed that pulmonary function prior to allo‐HCT is a valuable predictor of patient mortality following allo‐HCT, which is consistent with previous reports . Notably, the small airway disease parameter trueV˙50/trueV˙25 is the strongest predictor of survival; it has a much higher predictive value than %FEV1.0 and FEV 1.0/FVC, which mainly reflect central airway obstruction.…”
Section: Discussionsupporting
confidence: 92%
“…Some investigators have demonstrated that lung function evaluated prior to allogeneic hematopoietic cell transplantation (allo‐HCT) is useful to identify patients at risk for pulmonary complications or death . However, the proportion of patients eligible for allo‐HCT who show significant abnormalities in the pulmonary function test (PFT) – specifically, percent predicted forced expiratory volume in 1 s (%FEV1.0) and percent predicted vital capacity (%VC) – before allo‐HCT is low.…”
Section: Introductionmentioning
confidence: 99%
“…[88][89][90][91] For this patient, we would initiate comprehensive pulmonary function evaluation as results of pulmonary function tests are predictive for long-term outcome of allo-HCT. 92,93 If the patient has a comorbidity score of 3 or greater, and this is consistent with the bedside clinical assessment, we would initiate induction therapy with hypomethylating agents. We would not ordinarily proceed with allogeneic transplantation in this setting.…”
Section: Questionsmentioning
confidence: 82%
“…Previous studies have reported markedly impaired pulmonary function after HSCT with frequencies varying from 24% up to 83% with abnormal baseline spirometry predicting post‐HSCT abnormality. Most studies documented mainly restrictive dysfunction in HSCT patients as observed in our patient population.…”
Section: Discussionmentioning
confidence: 99%